Circulating (CD3−CD19+CD20−IgD−CD27highCD38high) Plasmablasts: A Promising Cellular Biomarker for Immune Activity for Anti-PLA2R1 Related Membranous Nephropathy? - Agnieszka Pozdzik; Ingrid Beukinga; Chunyan Gu-Trantien; Karen Willard-Gallo; Joëlle Nortier; Olivier Pradier (Mediators of Inflammation)
Membranous nephropathy (MN) is a kidney specific autoimmune disease mainly mediated by anti-phospholipase A2 receptor 1 autoantibody (PLA2R1 Ab). The adequate assessment of chimeric anti-CD20 monoclonal antibody, rituximab (RTX), efficacy is still needed to improve clinical outcome of patient with MN. We evaluated the modification of plasmablasts (CD3−CD19+CD20−IgD−CD27highCD38high), a useful biomarker of RTX response in other autoimmune diseases, and memory (CD3−CD19+CD20+IgD−CD27+CD38−) and naive (CD3−CD19+CD20+IgD+CD27−CD38low) B cells by fluorescence-activated cell sorter analysis in PLA2R1 related MN in one patient during the 4 years of follow-up after RTX. RTX induced complete disappearance of CD19+ B cells, plasmablasts, and memory B cells as soon as day 15. Despite severe CD19+ lymphopenia, plasmablasts and memory B cells reemerged early before naive B cells (days 45, 90, and 120, resp.). During the follow-up, plasmablasts decreased more rapidly than memory B cells but still remained elevated as compared to day 0 of RTX. Concomitantly, anti-PLA2R1 Ab increased progressively. Our single case report suggests that, besides monitoring of serum anti-PLA2R1 Ab level, enumeration of circulating plasmablasts and memory B cells represents an attractive and complementary tool to assess immunological activity and efficacy of RTX induced B cells depletion in anti-PLA2R1 Ab related MN.